Estudo comparativo da fotoluminescência dos picratos de európio (III) com a 2-aza-ciclooctanona e N-metil-cicloheptanona - Macrino, Clebson de Jesus (2013)
This paper describes the synthesis and characterization of compounds of lanthanide (III) picrates, Ln(pic)3], pic = C6H2N3O7e (Ln = Eu e Gd) with 2-aza-cyclooctanone, C7H13NO, (OEN), e N-methyl-2-aza-cycloheptanone, C6H10NO(CH3),(NMK).The compounds of stoichiometry [Eu(pic)3.(H2O)11], [Eu(pic)3.(OEN)3],[Eu(pic)3.(NMK)3], [Gd(pic)3.(H2O)11], [Gd(pic)3.(OEN)3] and[Gd(pic)3.(NMK)3] have been synthesized and characterized by microanalytical procedures, infrared and measures luminescence.The presence of bands ?assNO2and ?SNO2due to picrates ions and the frequency shift of ?CO stretching lactams presented in the vibrational spectrum of compounds to lower energy regions indicate the coordination of the ligands to the metal center lanthanide. The effect of replacing binders respective 2-aza-cyclooctanone and N-methyl-2-aza-cycloheptanone the compound of europium (III) picrate hydrate was investigated to verify the influence luminescent properties of these ligands on their respective complexes. Were observed in their emission spectra transitions characteristic of Eu3+ion. The triplet states of the ligands were obtained through the emissionspectra of gadolinium compounds, thus allowing to correlate them with the emitter 5D0level of Eu3+ion. The experimental intensities parameters of the Judd-Ofelt(O2and O4) and R02were determined in order to evaluate the degree of covalency of the compounds and the effect of field strength on the binder Eu3+ion. The spontaneous radiative decay rate (Arad), non radiative (Anrad), lifetime (t) and quantum efficiency (?) were calculated and correlated with the compounds prepared in order to evaluate the efficiency of emission of each compound. The chromaticity diagram was used to assess the purity of the emission of each compound. The structure of the compound [Eu(pic)3.(OEN)3] was determined using the technique of X-ray diffraction by the method of monocrystal which allowed the structure to make a correlation with the respective emissionspectrum of the compound